Preparation, structure and properties of nanocomposite membranes prepared by phase inversion - Adamczak, Michał; Kamińska, Gabriela; Bohdziewicz, Jolanta (Polimery, 2021)
Preparation, structure and properties of nanocomposite membranes prepared by phase inversion The article is a review of the literature related to the techniques of preparation, structure and properties of the membranes obtained from polymer solutions modified with nanoparticles. The incorporation of nanomaterials influences the structure and physicochemical properties as well as transport and separation characteristics of the produced membranes. The current state-of-the-art in the field of polymer nanocomposite membranes prepared by phase inversion is presented.